(untitled) (Castilla. Estudios de Literatura, 2021)
Many scholars have tried to define accurately the fantastic. Nevertheless, this paper intends to draw the attention over an aspect somehow neglected: the function of the fantastic in a dialogical relationship with many other fiction genres such as hard-boiled detective novels, urban legends, science-fiction books, or thrillers, all considered to be narrative devices used to talk in an indirect way about traumatic events. All this can be illustrated with a close reading of Parque Chas, an Argentinian comic by Barreriro and Risso, published in the magazine Fierro